Macrophage Activation Syndrome in Adults: A Retrospective Case Series. (June 2021) - Warmoth, Taylor; Ramesh, Malvika; Iwuji, Kenneth; Pixley, John S.
Macrophage activation syndrome (MAS) is a form of hemophagocytic lymphohistocytosis that occurs in patients with a variety of inflammatory rheumatologic conditions. Traditionally, it is noted in pediatric patients with systemic juvenile idiopathic arthritis and systemic lupus erythematous. It is a rapidly progressive and life-threatening syndrome of excess immune activation with an estimated mortality rate of 40% in children. It has become clear recently that MAS occurs in adult patients with underlying rheumatic inflammatory diseases. In this article, we describe 6 adult patients with likely underlying MAS. This case series will outline factors related to diagnosis, pathophysiology, and review present therapeutic strategies.